Pengembangan Kurikulum Bahasa Arab Berparadigma Integrasi-Interkoneksi Mengacu KKNI dan SN-DIKTI - Syindi Oktaviani R Tolinggi (Universitas Islam Negeri Palangka Raya, 2020)
The purpose of this article is to examine the development of integrated and interconnected paradigm based curriculum of the Arabic education based on KKNI and SN-Dikti. (1) Have the curriculum structure of the study program been prepared in accordance with the needs of students who will face challenges in society as the aim of the KKNI formulation?, (2) Is the depth and freedom of lecture material in accordance with the KKNI guidebook and curriculum preparation manual for high education?. This article is a type of library research with qualitative research method because the data source in this study is a curriculum document that was developed referring to KKNI and SN-Dikti in the PBA UIN Suka Yogyakarta Master